2016
DOI: 10.17691/stm2016.8.4.13
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the Hypoplastic Variant of Chronic Endometritis: Arguments Against Antibacterial Therapy

Abstract: The aim of the investigation was to provide a rationale for refusal from antibacterial therapy in the hypoplastic variant of chronic endometritis.Materials and Methods. The study involved 116 patients with burdened reproductive history (infertility, miscarriage, IVF and ET failures), who were diagnosed with the hypoplastic variant of chronic endometritis after complex examination (hysteroscopy, morphology and immunohistochemistry of the endometrium). The study was carried out in two stages. At the first stage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…By consensus of obstetricians and gynaecologists in 2006 each case of nondeveloping pregnancy is regarded as being associated with chronic endometritis, both at the cause and the effect levels [7] Latest research has shown that chronic pelvic inflammatory diseases are not accompanied by disruption of parameters of cellular and humoral immunity detected in peripheral blood. Thus, in order to determine functional status of endometrium, we need to assess the local immunity [8][9][10]. Bacterium-virus colonization of endometrium is the result of failure of the immune system to eliminate infectious agent; but at the same time its spread is limited due to effector properties of Tlymphocytes, NK-cells and macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…By consensus of obstetricians and gynaecologists in 2006 each case of nondeveloping pregnancy is regarded as being associated with chronic endometritis, both at the cause and the effect levels [7] Latest research has shown that chronic pelvic inflammatory diseases are not accompanied by disruption of parameters of cellular and humoral immunity detected in peripheral blood. Thus, in order to determine functional status of endometrium, we need to assess the local immunity [8][9][10]. Bacterium-virus colonization of endometrium is the result of failure of the immune system to eliminate infectious agent; but at the same time its spread is limited due to effector properties of Tlymphocytes, NK-cells and macrophages.…”
Section: Introductionmentioning
confidence: 99%